Implementasi Peraturan Pemerintah No 49 Tahun 2018 pada Kantor Urusan Agama Kecamatan Batu Kementerian Agama Kota Batu - Nurul Azizah; Suyeno; Langgeng Rahmatulllah Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the most important things in running the government and meeting the needs of the community is the institutions in the regions. If the institution runs well and correctly, it will certainly benefit a lot and bring a lot of good. However, if on the contrary, it will only benefit some people who are close so that it can be said that the institution is less running. Therefore, institutions in which or can be said to be civil servants and the like must work properly as government regulations have been set. The research method used is qualitative with a descriptive approach. The results obtained that the work ethic and performance of the Batu Subdistrict Religious Affairs Office are in accordance with government regulation No. 49 of 2018. Where the suitability is based on the implementation from superiors to staff and administration so that reports and activities and tasks are carried out properly. The obstacles that arise are also not many, just continue to provide the best service for the community so that innovations in adjusting technology are always carried out, such as online absences, online and remote submissions, etc. with the aim of making it easier for people in need.